2022
DOI: 10.3168/jds.2021-20860
|View full text |Cite
|
Sign up to set email alerts
|

Removing data and using metafounders alleviates biases for all traits in Lacaune dairy sheep predictions

Abstract: Bias in dairy genetic evaluations, when it exists, has to be understood and properly addressed. The origin of biases is not always clear. We analyzed 40 yr of records from the Lacaune dairy sheep breeding program to evaluate the extent of bias, assess possible corrections, and emit hypotheses on its origin. The data set included 7 traits (milk yield, fat and protein contents, somatic cell score, teat angle, udder cleft, and udder depth) with records from 600,000 to 5 million depending on the trait, ~1,900,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In setting parents of the validation animals to missing, the relationship between genotyped and non-genotyped animals might become zero (i.e., A 12 = 0) and in such situation, H −1 will not contribute to the estimation of group effects ( Tsuruta et al, 2019 ). Truncation of the data set, e.g., only considering data after the year 2000, may also reduce the number of genetic groups, and has been found to reduce prediction biases ( Cesarani et al, 2021 ; Hidalgo et al, 2021 ; Hollifield et al, 2021 ; Macedo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In setting parents of the validation animals to missing, the relationship between genotyped and non-genotyped animals might become zero (i.e., A 12 = 0) and in such situation, H −1 will not contribute to the estimation of group effects ( Tsuruta et al, 2019 ). Truncation of the data set, e.g., only considering data after the year 2000, may also reduce the number of genetic groups, and has been found to reduce prediction biases ( Cesarani et al, 2021 ; Hidalgo et al, 2021 ; Hollifield et al, 2021 ; Macedo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Granado-Tajada et al (2020) found that bias in dairy sheep evaluations was greater for HBLUP than ABLUP, although the difference was not statistically significant. Macedo, Christensen, et al (2020) reported the least bias for HBLUP with MF, as did Macedo et al (2022) using a method of construction based on inbreeding trend over time.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies suggested that truncating datasets that trace many generations of pedigrees for the estimation of breeding values may help to reduce level and dispersion bias more than fitting genetic groups. In a dairy sheep population, Macedo et al (2022) compared different strategies to model genetic groups and studied the effects on level and dispersion bias. The best strategy to reduce level bias and over-dispersion in their dataset was to truncate old pedigree and phenotypic data.…”
Section: Usage Of Genetic Groups In Interbeef Evaluationsmentioning
confidence: 99%
“…Truncating data yielded better results compared to modelling genetic groups while using the full dataset in either pedigree or single-step genomic evaluations. Macedo et al (2022) suggested that the accumulation across generations of small noises or approximations during the estimation of breeding values could lead to a snowball effect, resulting in bias and dispersion of younger animals' EBV. Truncating the data was an effective solution to alleviate this problem in their study.…”
Section: Usage Of Genetic Groups In Interbeef Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation